Thermal effects on flow and salinity distributions in heterogeneous coastal aquifers with fixed-flux inland boundaries - Yu, Xiayang; Xin, Pei; Pu, Li (Frontiers in Environmental Science, 2022)
Freshwater-seawater (FW-SW) temperature contrasts widely exist in natural coastal aquifers. The significant effects of thermal forcing on water flow and salinity distributions for homogeneous aquifers have been demonstrated recently, however, the impact on heterogeneous aquifers remains unclear. This study conducted simulations of variable-density flow, and heat and salt transport with Monte-Carlo realizations of log-normally distributed permeability fields to examine such impacts. The averaged results showed that warmer freshwater could lead to a significant landward intrusion of freshwater-seawater interface in the heterogeneous aquifer. The random permeability fields increased the thermal effects of warmer freshwater and thus facilitated landward seawater intrusion. Furthermore, under warmer seawater conditions, salt dispersion was enhanced and density effects were reduced in heterogeneous coastal aquifers, thus altering the two opposing seawater circulation cells induced by double diffusion of salt and heat. The clockwise seawater circulation was strengthened whereas the anticlockwise one was weakened. Sensitivity analyses showed that an increased variance of permeability field further inhibited the anticlockwise seawater circulation cell caused mainly by heat diffusion. A larger correlation length of permeability field facilitated the thermal effect on the salinity distribution, increasing the associated uncertainty range caused by FW-SW temperature contrasts.